Analisis Penjualan dan Perputaran Pada Pertumbuhan Modal Kerja Terhadap Daya Laba Pt. Ace Hardware Indonesia, Tbk Tahun 2019-2022. - Villya Marsheela Putri; Ratih Kusumastuti (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The purpose of this study is for companies to analyze the effect of the variable growth of working capital turnover and sales on company profitability. In this study, researchers used financial report data from PT. Ace Hardware Indonesia, Tbk. and The data used in this research is secondary data from 2019-2022. The data collection method itself uses the documentation method. Where the results of this study have a significant effect on profitability while working capital has a negative and significant effect on profitability. In this study, researchers recommend that companies can utilize and also process resources so that they are effective in order to increase profits from the company so that increased profitability of the company can be achieved.